2006
DOI: 10.1200/jco.2006.24.18_suppl.2047
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic interaction and safety of enzastaurin and pemetrexed in patients with advanced or metastatic cancer

Abstract: 2047 Background: Enzastaurin, an orally administered potent PKC inhibitor, is an anti-angiogenic agent that also suppresses PI3K/AKT to inhibit tumor cell proliferation and induce tumor cell death. Preclinical data suggest that the combination of enzastaurin and pemetrexed (Alimta) produced additive or synergistic antitumor activity in tumor specimens. This phase 1b study evaluated the safety, pharmacokinetic (PK) interaction, and antitumor activity of enzastaurin when combined with pemetrexed. Methods: Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…46 Therefore, clinical trials evaluating enzastaurin in combination with other cytotoxic agents are currently being pursued, especially because enzastaurin does not add to the toxicity of cytotoxic agents. [47][48][49] In conclusion, this phase II study of single-agent enzastaurin as second-or third-line therapy in patients with metastatic NSCLC has shown disease stabilization for 6 months in 13% of patients and prolonged stabilization ranging from 7 to 20 months in six of 55 patients. Future single-agent enzastaurin trials should focus on the identification of potential markers to tailor enzastaurin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…46 Therefore, clinical trials evaluating enzastaurin in combination with other cytotoxic agents are currently being pursued, especially because enzastaurin does not add to the toxicity of cytotoxic agents. [47][48][49] In conclusion, this phase II study of single-agent enzastaurin as second-or third-line therapy in patients with metastatic NSCLC has shown disease stabilization for 6 months in 13% of patients and prolonged stabilization ranging from 7 to 20 months in six of 55 patients. Future single-agent enzastaurin trials should focus on the identification of potential markers to tailor enzastaurin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,20,31 The synergic antitumor activity of enzastaurin and pemetrexed combination was shown in NSCLC cell lines, 18 -20 and previous combination studies of enzastaurin with cytotoxic agents showed neither increased toxicity nor PK drug-drug interactions. 15,16,31,32 Therefore, in this study, we decided to assess safety of the recommended clinical doses of enzastaurin and pemetrexed (enzastaurin 500 mg/d and pemetrexed 500 mg/m 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…33 The PK results of this study indicated no significant PK interaction between enzastaurin and pemetrexed, which was consistent with a previously published phase I study report. 32 One possible reason for the absence of any effect on pharmacokinetics was the different pathways used for elimination. Pemetrexed is renally eliminated, whereas a phase I study using [ 14 C] enzastaurin indicated that enzastaurin undergoes extensive hepatic metabolism with minimal renal elimination (Eli Lilly and Company, Internal Clinical Study Report, October 2006).…”
Section: Discussionmentioning
confidence: 99%